Exploring the construct of meaning in life among the senior undergraduate student - Farida Agus Setiawati; Edi Purwanta (Institute of Advanced Engineering and Science, 2023)
The meaning in life is a fundamental human behavior that plays an essential role in self-development. The concept of meaning in life continues to focus on researchers using various theoretical perspectives. This study explored the construct of meaning in life from the vantage point of undergraduate students in their final year. They were chosen by considering the severity of the developmental tasks that must be completed during this time. By using the mixed-method approach, the study found the concept of meaning in life through the qualitative method. Some themes were related to the meaning of life, namely: experiencing a number of important events, being devoted to religion, learning from life, feeling positive emotions, benefiting others, interacting socially, and caring for oneself. The study was followed by a quantitative method through exploratory factor analysis and found that the construct of the meaning in life consisted of three factors, namely: facing difficult and severe situations, getting lessons from unpleasant situations, and thinking flexibly when dealing with various situations. This measurement model could be used in the development of meaning in life theory. Practically, it becomes the reference in solving the life problems.